Многоязычие добровольное, естественное или принудительное: Поляки в Кишиневе - Krasowska, Helena (Theoria et Historia Scientiarum, 2024)
The article describes different types of multilingualism of Poles in Chisinau. The author comes to the conclusion that the voluntary multilingualism among the Poles in Chisinau was caused by several factors, first of all, it was inspired by the language policy implemented in school education, in administration. Polyakov Chisinau also characterizes the natural multilingualism that arose as a result of mixed marriages. Among the Poles of Chisinau, we also encounter a kind of imposed multilingualism, when the authorities introduced the Moldovan language into schools, state-administrative institutions, but the Russian language was also imposed, as mentioned by the respondents. As a result, a language conflict arose not only in Chisinau, but also in the Republic of Moldova as a whole. The language conflict is thus a consequence of political conflicts in the state.